Spiritualitas, Regulasi Diri, dan Kesejahteraan Subjektif Siswa Sekolah Menengah Atas - Leonita Ikasari Saputri D.; Fuad Nashori (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2023)
This study aims to determine the influence of spirituality and self-regulation on the subjective well-being of high school students. This research used a quantitative approach with multiple linear regression analysis. The participants were 404 high school students in Kebumen Regency, Central Java, Indonesia. The results show that spirituality and self-regulation simultaneously have a significant positive influence on subjective well-being by 28%. Partially, spirituality and self-regulation have a significant effect on subjective well-being with a greater influence from self-regulation (16.3%) than spirituality (11.6%).